Identification of CD8+ T-cell epitope from multiple myeloma-specific antigen AKAP4 - Ma, Ning; Liu, Huihui; Zhang, Yang; Liu, Wei; Liang, Zeyin; Wang, Qian; Sun, Yuhua; Wang, Lihong; Li, Yuan; Ren, Hanyun; Dong, Yujun (Frontiers in Immunology, 2022)
Multiple Myeloma (MM) is a malignant plasma cell disorder affecting mainly the elderly population. Revolutionary progress in immunotherapy has been made recently, including monoclonal antibodies and chimeric antigen receptor T cell (CAR-T) therapies, however, the high relapse rate remains problematic. Therefore, Combination therapies against different targets would be a reasonable strategy. In this study, we present a new X-chromosome encoded testis-cancer antigen (CTA) AKAP4 as a potential target for MM. AKAP4 is expressed in MM cell lines and MM primary malignant plasma cells. HLA-A*0201-restricted cytotoxic T lymphocytes (CTLs) induced by dendritic cells (DCs) transduced with an adenovirus vector encoding the full-length AKAP4 gene were demonstrated to lyse AKAP4+ myeloma cells. Seven of the 12 candidate epitopes predicated by the BIMAS and SYFPEITH algorithms were able to bind HLA-A*0201 in the T2 binding assay, of which, only two peptides were able to induce CTLs cytotoxicity in the co-culture of peptides-loaded human mature dendritic cells and the autologous peripheral blood mononuclear cells (PBMCs) from the same HLA-A*0201 donor. The AKAP4 630-638 VLMLIQKLL was identified as the strongest CTL epitope by human IFN-γ ELISPOT assay. Finally, the VLMLIQKLL-specific CTLs can lyse HLA-A*0201+AKAP4+ myeloma cell line U266 in vitro, inhibit tumor growth in the mice bearing U266 tumors in vivo. These results suggest that VLMLIQKLL epitope could be used to develop cancer vaccine or T cell receptor transgenic T cells (TCR-T) to kill myeloma cells.